A Critical Analysis on ‘Theory of Knowledge’ (Epistemology) of Charaka Samhita and its Importance in Clinical Medicine - Paul, Sumana Ray; Ray, Sukalyan (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Epistemology, that is, “theory of knowledge” or Pramana Vigyana is considered as one of the three fundamental division of any philosophy. The metaphysical analysis and ethical conclusion of any philosophical school depend on its theory of knowledge. Charaka Samhita having a unique philosophical background which is conglomeration of different philosophical doctrines from all the major Indian philosophical schools also depends on its own epistemology while propounding the principles of Ayurveda. Understanding the different Pramana, that is, sources of knowledge as discussed in this compendium helps us to understand the subject better and their subsequent application in clinical medicine for benefit of mankind. The present study was carried out to evaluate the different Pramana or sources of knowledge as discussed in Charaka Samhita and also to evaluate their subsequent application in the field of clinical medicine. Discussion: Charaka Samhita has propounded four principal Pramana such as: (1). Aptopadesha (scriptural testimony) (2), Pratyaksham (sensory perception) (3), Anumana (inference), and (4). Yukti (reasoning). Along with these four sources of knowledge, it also discussed other Pramana briefly such as: Aoupamya (comparison), Aitihya (ethical guidance by authoritative persons and scriptures), and Arthaprapti (implied meaning). But throughout the compendium, Acharya Charaka has given most importance to three Pramana like Aptopadesha followed by Pratyaksha followed by Anumana. The understandings of all these Pramana are mainly based on Nyaya philosophy although the chronology follows the Samkhya tradition. What makes the epistemology of Charaka Samhita a unique one is its clinical implementation as discussed by Acharya Charaka in relation with every Pramana. Conclusion: Understanding the various Pramana as discussed in Charaka Samhita along with their clinical implementation helps us to realize the profound philosophical background of this compendium. It also paves the way for more innovative research as how to apply this eternal knowledge of epistemology for advancement of medical science.